Assessing the Success of CSR Using the Social Return on Investment (SROI) Approach: A Case Study of PT. Borneo Indobara’s Fishermen Community Empowerment Program in Angsana Trans Nelayan Village - Hasan, Ali; Ginting, Henndy (Jurnal Syntax Transformation, 2025)
This study aims to develop the Corporate Social Responsibility (CSR) program of PT Borneo Indobara through a case study of the Kenari Jaya Program in Trans Nelayan Angsana Village, Tanah Bumbu Regency, South Kalimantan. The program is designed to empower the fishermen community in economic, social, and environmental aspects through the provision of fish aggregating devices (rumpon), training, and fisheries infrastructure development. This research employs a qualitative exploratory approach by collecting data through in-depth interviews, field observations, and document analysis. The findings indicate positive impacts of the program on increasing fishermen’s income, improving fishing time efficiency, and diversifying family economic activities through home industry groups. The study also identifies challenges such as uneven distribution of benefits, lack of technical training, and limited local economic institutions. SWOT analysis and Fishbone Diagram were used to identify root causes and formulate development strategies to make the program more inclusive, sustainable, and socially impactful. Recommendations include strengthening fishermen’s cooperatives, expanding training coverage, and developing alternative community-based development programs. The results are expected to serve as a reference for developing CSR programs based on coastal community empowerment in Indonesia.